Selectively enhancing radiosensitivity of cancer cells via in situ enzyme-instructed peptide self-assembly - Yang Gao; Jie Gao; Ganen Mu; Yumin Zhang; Fan Huang; Wenxue Zhang; Chunhua Ren; Cuihong Yang; Jianfeng Liu (Elsevier, 2020)
The radiotherapy modulators used in clinic have disadvantages of high toxicity and low selectivity. For the first time, we used the in situ enzyme-instructed self-assembly (EISA) of a peptide derivative (Nap-GDFDFpYSV) to selectively enhance the sensitivity of cancer cells with high alkaline phosphatase (ALP) expression to ionizing radiation (IR). Compared with the in vitro pre-assembled control formed by the same molecule, assemblies formed by in situ EISA in cells greatly sensitized the ALP-high-expressing cancer cells to γ-rays, with a remarkable sensitizer enhancement ratio. Our results indicated that the enhancement was a result of fixing DNA damage, arresting cell cycles and inducing cell apoptosis. Interestingly, in vitro pre-formed assemblies mainly localized in the lysosomes after incubating with cells, while the assemblies formed via in situ EISA scattered in the cell cytosol. The accumulation of these molecules in cells could not be inhibited by endocytosis inhibitors. We believed that this molecule entered cancer cells by diffusion and then in situ self-assembled to form nanofibers under the catalysis of endogenous ALP. This study provides a successful example to utilize intracellular in situ EISA of small molecules to develop selective tumor radiosensitizers.